1990
DOI: 10.1159/000186160
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hyperuricemic Nephropathy and Renal Failure after Transplantation

Abstract: This report describes a patient who was treated for rejection of a cadaveric renal allograft with a variety of drugs, including the continuous administration of ciclosporin over a period of 16 months. The patient developed hyperuricemia, attacks of gout and finally a rapidly progressing renal failure 17 months after transplantation. The removed transplanted kidney showed extensive tubular dilatation, intratubular deposits of uric acid crystals and characteristic granulomas. There was also morphologic evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Evidence that hyperuricemia causes or contributes to progressive kidney disease or CVD is weak, even in the general population (804,818,819). Acute kidney injury from very high uric acid levels has been reported (820). A large registry cohort study recently demonstrated an association of gout with elevated mortality (adjusted hazard ratio 1.26, 95% CI 1.08–1.47) and graft loss (adjusted hazard ratio 1.22, 95% CI 1.01–1.49) (808).…”
Section: Rationalementioning
confidence: 99%
“…Evidence that hyperuricemia causes or contributes to progressive kidney disease or CVD is weak, even in the general population (804,818,819). Acute kidney injury from very high uric acid levels has been reported (820). A large registry cohort study recently demonstrated an association of gout with elevated mortality (adjusted hazard ratio 1.26, 95% CI 1.08–1.47) and graft loss (adjusted hazard ratio 1.22, 95% CI 1.01–1.49) (808).…”
Section: Rationalementioning
confidence: 99%
“…Reports of immunofluorescence have been in patients with gout and co-existent kidney disease, including cellular rejection and transplant glomerulopathy following renal transplantation [114], or drug-induced glomerulonephritis [115]. In patients with membranous nephropathy and gout, granular deposits of IgG, C3 and renal tubular epithelium antigen were observed in the glomerular capillary wall [108].…”
Section: Resultsmentioning
confidence: 99%
“…In most cases hy peruricemia was asymptomatic; however, in some reports 7-11% of cases had clinical symptoms of gout [14,15]. Venkataseshan et al [16] described a case of kidney trans plant failure with graft loss, due to acute hyperuricemic nephropathy while on CyA therapy. Hyperuricemia in patients on CyA is caused by a tubular urate transport defect.…”
Section: Discussionmentioning
confidence: 99%